2015
DOI: 10.2139/ssrn.2564667
|View full text |Cite
|
Sign up to set email alerts
|

Immigration and Innovation: Chinese Graduate Students in U.S. Universities

Abstract: Immigration is rapidly changing the composition of the R&D workforce in the United States, with important implications for both management and public policy. We study here the Chinese chemists and chemical engineers who migrate to the United States for their graduate studies. We analyze productivity at the individual researcher level, thus bypassing the identification issues that earlier studies had to confront when analyzing the relationship between immigration and innovation at the university or firm level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Third, we contribute to the literature on academic mobility. Seminal contributions in this area have shown that mobile researchers have higher productivity (Franzoni et al, 2014;Gaulé and Piacentini, 2013;Hunter et al, 2009;Stephan and Levin, 2001), and broader international collaboration networks (Scellato et al, 2015) than non-mobile researchers. However, it remains unexplored what are the effects of financial support to mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we contribute to the literature on academic mobility. Seminal contributions in this area have shown that mobile researchers have higher productivity (Franzoni et al, 2014;Gaulé and Piacentini, 2013;Hunter et al, 2009;Stephan and Levin, 2001), and broader international collaboration networks (Scellato et al, 2015) than non-mobile researchers. However, it remains unexplored what are the effects of financial support to mobility.…”
Section: Introductionmentioning
confidence: 99%